Upaya Peningkatan Hasil Belajar IPA Melalui Metode Card Sort Kelas IV di MI Al Hidayah Rawa Denok Depok - Ernawati; Wasiatul Jannah; Helentina Mena; Zuhana; Daden Jamaludin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the improvement of science learning outcomes through the use of the Card Sort strategy in fourth-grade students of MI Al Hidayah Rawa denok Depok. The method used is Classroom Action Research (CAR) with a descriptive approach. The research subjects were 19 fourth - grade students. The study was conducted in two cycles. In the first cycle, 11 students (57.89%) achieved mastery learning. In the second cycle, the number increased to 18 students (94.73%). These results indicate that the Card Sort strategy is effective in improving science learning out comes in fourth-grade students at MI Al Hidayah Rawadenok, Pancoran Mas District, Depok City, West Java.